Perbedaan Pengaruh Kinesio Taping dan Neuromuscular Taping Terhadap Penurunan Nyeri Punggung Bawah - Hammami, Yunan Nasrul; , Totok Budi Santoso, SST. FT., MPH (2017)
Background: One of the work related musculoskeletal disorder is lower back pain (LBP). Lower back pain on school staffs can arise from its activities to teach at the school with inappropriate work posture. The results showed that 18.9% of primary school teachers complained for having lower back pain. Complaints of pain in primary school teachers can be reduced with the kinesio taping method which is one of the modalities of physiotherapy that corrects and improves musculoskeletal disorders. Kinesio taping in its development are having some modifications e.g. neuromuscular taping (NMT). Objectives: The research aims to determine differences in the results of reducing kinesio taping and neuromuscular taping for decreasing lower back pain on teachers at SD 16 Muhammadiyah Surakarta and SD Muhammadiyah Program Khusus Kottabarat Surakarta. Methods: The method of this research was case study with A-B-A-B design. A was the measuring phase and the B was an action therapy phase. Data analysis techniques that will be used in this research is a descriptive analysis, where data are obtained as described later in the analysis and drawn a conclusion. Test that is used for independent groups were Mann-Whitney test, with 2 different groups: group 1 (kinesio taping) and group 2 (neuromuscular taping). Research results: Based on the results of the treatment that has been done, the researchers obtained the result that kinesio taping and neuromuscular taping equally have influence to decrease lower back pain. Statistical tests to test the different influence of kinesio taping and neuromuscular taping using Mann Withney U obtained p = 0.308 (> 0.05). Conclusion: From these data, it can be concluded that there is no significant difference between the kinesio taping and neuromuscular taping in reducing lower back pain on primary school teachers.